Innovative education training program of hajj healthcare workers improves the outcomes of Indonesian elderly hajj pilgrims - Probosuseno Probosuseno; Fidiansjah Fidiansjah; Wasilah Rochmah; Ali Ghufron Mukti (LPMPP Universitas Negeri Yogyakarta, 2022)
The ability of the Muslim community in Indonesia to perform the hajj pilgrimage, which fulfills Islam’s fifth pillar, is increasing. With the rise in life expectancy, the number of Indonesian elderly hajj pilgrims (EHP) is consequently growing. However, chronic conditions such as impairments, illnesses, and diseases cause an increase in morbidity and mortality among EHP. Thus, an innovative training program with practical tips for a healthy hajj experience is needed to improve the healthcare service to the EHP. This study aims to investigate the effects of an innovative training on the performance of Hajj Healthcare Workers of Indonesia (HHWI) and on the clinical outcomes of EHP. It was a quasi-experimental study. The population was all HHWI from the Surakarta embarkation in 2014. Meanwhile, the sample of this study was all 21 HHWI from Yogyakarta who received innovative training consisting of EHP special care training (theory and practice) in addition to basic national training. Twenty-one HHWI from Surakarta were randomly chosen as a control group and only received basic national training. Pre and post tests were used to assess knowledge of HHWI after training. The average pretest scores of the intervention and control groups were 48.50 and 48.07, respectively (p= 0.337), while the posttest score of the intervention group was 86.83 (p = 0.033). The measured parameters were the performance of HHWI, which is reflected by the EHP mortality rate, the number of outpatients, and the number of patients referred to the outpatients. We included the EHP under the supervision of HHWI, which has acquired training. EHP morbidity was evaluated as the number of outpatients and referred patients. There were 2216 outpatients from the intervention group as compared with 2144 in the control group, with most of them being 60-70 years old (p= 0,075). The number of referred EHP in the intervention and control groups was 10 and 30 patients, respectively (OR 2.94; p= 0.002). As for the mortality cases, we observed 7 EPH deaths during the hajj period (2 EPH from the intervention group vs 5 EPH from the control group; OR 0.263; p=0.207). Innovative training could reduce referral morbidity and mortality among elderly hajj pilgrims